Decrease of Serum IGF-1 Level is Not Associated With Obstructive Sleep Apnea in Fibromyalgia Patients - Emrullah HAYTA,; Ayşe Altun OKŞAŞOĞLU, (Archives of Rheumatology, 2017)
Objectives: This study aims to investigate the relationship of serum insulin-like growth factor 1 (IGF-1) level with obstructive sleep apnea, the Pittsburgh sleep quality index (PSQI), age, body mass index, and fibromyalgia impact questionnaire (FIQ) in fibromyalgia syndrome (FMS) patients. Patients and methods: A total of 105 female patients (mean age 41.8±9.0 years; range 26 to 55 years) with fibromyalgia (FMS group) who were diagnosed according to 2010 American College of Rheumatology criteria, and 51 female patients (mean age 39.9±10.8 years; range 24 to 54 years) with mechanical low back pain (MLBP) (control group) were included in the study. Age, smoking, educational status, tender point number, body mass index, duration of disease, FIQ, PSQI, and polysomnographic assessment of both FMS and control groups were recorded. Results: Sleep disorder was detected in 88 patients in FMS group and 15 patients in control group (p<0.05). The PSQI score was higher in the FMS group compared to the control group (9.9±4.6 vs. 5.7±3.5). The FIQ score was higher in the FMS group compared to the control group (53.4±17.4 vs. 26.4±13.9; p<0.05). The serum IGF-1 level of FMS group was significantly lower than that of the control group (140.6±49.5 ng/mL vs. 177.2±58.5 ng/mL; p<0.05). In the FMS group, an examination of the correlation between serum IGF-1 level with the age, body mass index, obstructive sleep apnea syndrome, FIQ, and PSQI revealed a negative correlation between serum IGF-1 with the age and PSQI. The obstructive sleep apnea syndrome ratios of study groups were comparable with regard to the frequencies of mild, moderate, and severe obstructive sleep apnea syndrome. Conclusion: In FMS patients, serum IGF-1 levels may decrease due to age and PSQI; however, this may not be related to the severity of obstructive sleep apnea.